PENGARUH FEAR OF MISSING OUT, ELECTRONIC WORD OF MOUTH, DAN BRAND IMAGE TERHADAP IMPULSIVE BUYING PRODUK SKINCARE - Putri, Anggun Anggita Kinasih Sunowo; Hanum Indriati , Inayat; Ratna Ningrum, Natalia (PRIMA EKONOMIKA, 2026)
This study aims to examine the impact of Fear of Missing Out (FOMO), brand perception, and electronic word of mouth (eWOM) on impulse buying behavior among skincare product consumers. This phenomenon is becoming increasingly important as digital trends and virality of content on social media influence impulse buying decisions. This study employed a quantitative methodology using an online survey instrument administered to 130 participants who had acquired skincare products. The data were evaluated using SmartPLS 3.0. The results of the analysis revealed that brand perception and eWOM had a positive and significant influence on impulse buying, while FOMO showed no significant impact. Favorable brand perception stimulated consumer trust in the quality and safety of the product, thereby encouraging impulsive acquisition. Simultaneously, positive testimonials disseminated on social media (eWOM) were found to be a strong catalyst in inciting impulse buying decisions. These results reinforce the need for skincare companies to cultivate a strong brand image and strategically leverage eWOM to increase customer loyalty and purchase intention. This study pragmatically contributes to the formulation of more effective digital marketing strategies in promoting impulse buying, as well as addressing the research gap on the influence of FOMO, brand perception, and eWOM in the Indonesian skincare sector.